Stock return and inflation with supply and demand shocks: evidence from Malaysia - Hawati Janor; Ruzita Abdul Rahim; Mohd Hasimi Yaacob; Izani Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2010)
The study provides evidence on the validity of the Fisher hypothesis, linking inflation and stock returns using Malaysian data over a period of 27-year from 1980 to 2006. The puzzling negative relationship between stock returns and inflation in industrialized economies is well documented. However, similar studies in different economies such as the developing or the emerging markets are limited. Emerging markets have gained importance and interests from international investors as financial assets and these markets have been identified as a means of international diversification which is capable of offering good returns. With this motivation, understanding factors that may influence stock returns in these markets is crucial. We improve the testing power of current studies by conducting a test that includes the role of demand and supply shocks to inflation. In doing so, we utilize the Autoregressive Distributed Lag (ARDL) bounds test that is capable of testing for the existence of a long-run relationship between the variables irrespective of whether the time series are I(0) or I(1). Inconsistent with the Fisher hypothesis, we find no long-run relationship between inflation and stock return. However, when money supply and industrial production are incorporated in the model, we find that stock returns, industrial production and money supply are the “long run forcing” variables for the inflation. The finding that inflation is not significant in explaining stock returns may suggest that the investment perception in the Malaysian financial markets is quite different from that found in other markets. Unlike the later, the former which does not support the Fisher hypothesis is thus less likely to be sensitive to inflationary variables. Overall the study provides evidence on the importance of sources of inflation (i.e. demand and supply shocks) on stock returns-inflation relationship in Malaysian market.